0394 Efficacy and Safety in People With Narcolepsy Transitioning From Sodium Oxybate to Lower-Sodium Oxybate: Data From the Real-World TENOR Study. (25th May 2022) - Leary, Eileen; Zee, Phyllis; Fuller, Douglas; Macfadden, Wayne; Steininger, Teresa; Bae, Charles; Husain, Aatif
Abstract: Introduction: Lower-sodium oxybate (LXB) contains 92% less sodium than sodium oxybate (SXB) and is approved for treating cataplexy or excessive daytime sleepiness in patients with narcolepsy (aged ≥7 years) and idiopathic hypersomnia in adults. The Transition Experience of persons with Narcolepsy taking Oxybate in the Real-world (TENOR) study collects data from patients transitioning from SXB to LXB in a real-world setting. Methods: TENOR is a patient-centric, prospective, observational, noninterventional, virtual-format study (NCT04803786). Eligible participants include US adults with confirmed narcolepsy (type 1 or 2) transitioning from SXB to LXB within the previous/upcoming 7 days. Longitudinal data are collected for 21 weeks post-transition. Efficacy measures (Epworth Sleepiness Scale [ESS]; Functional Outcomes of Sleep Questionnaire, Short Version [FOSQ-10]; and British Columbia Cognitive Complaint Inventory [BC-CCI]) are collected at baseline (taking SXB) and weekly beginning at week 1 (taking LXB). Participants were prospectively queried about changes in tolerability. These analyses include data collected during the first week of LXB from all qualifying participants. Results: The analyses include 85 participants (type 1, n=45; type 2, n=40) at baseline and 79 participants at week 1. At baseline, mean (SD) age was 40.3 (13.0) years; most participants were female (73%) and White (87%), and 79% took ≥1 concomitant medication for narcolepsy at baseline in addition to SXB. Patient-reported comorbidities included depression (54%), anxiety (46%), obstructive sleep apnea (27%), and hypertension (24%). At baseline (taking SXB) and week 1 (taking LXB), mean (SD) ESS scores were 9.9 (5.2) and 9.7 (5.2), respectively (mean [SD] change: −0.3 [2.7]); mean (SD) FOSQ-10 scores were 28.7 (7.1) and 28.8 (7.5), respectively (mean [SD] change: 0.2 [3.9]); and mean (SD) BC-CCI scores were 6.1 (4.4) and 6.1 (4.7), respectively (mean [SD] change: 0.0 [2.3]). Tolerability associated with LXB treatment was consistent with the known safety profile of SXB. Conclusion: In this real-world study in people with narcolepsy who are transitioning from SXB to LXB, efficacy of oxybate treatment on measures of excessive daytime sleepiness, quality of life, and cognition as well as safety were maintained after 1 week. Longer-term maintenance of efficacy and safety will be reported at study completion. Support (If Any): Jazz Pharmaceuticals.